2020
DOI: 10.1515/jpm-2020-0228
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing cross transmission of SARS-CoV-2 in obstetric ultrasound during COVID-19 pandemic

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)–associated infection (COVID-19) is affecting populations worldwide. This statement may serve as guidance for infection prevention and safe ultrasound practices during the COVID-19 pandemic. Ultrasound examination is a fundamental part of obstetric care, yet it is a potential vector for transmission of SARS-CoV-2. Decontamination methods should always be implemented for ultrasound equipment, especially in the presence of suspected or confirmed COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…13 Researchers in another study used adenosine triphosphate testing to evaluate the cleanliness of ultrasound equipment at five facilities in Australia and found that 46.4% of samples of ultrasound gel bottles were dirty-that is, "definitely unclean." 14(p889) If there is concern about cross-contamination, such as when using gel on a patient who requires contact precautions or has a suspected or confirmed COVID-19 infection, 15 personnel should either discard the multidose container after use or use single-use packets. 3,4 Personnel should consider multidose ultrasound transmission gel containers to be high-touch objects 4 when cleaning the environment between patients and clean the container in accordance with facility policy and the manufacturer's IFU.…”
Section: Answermentioning
confidence: 99%
See 1 more Smart Citation
“…13 Researchers in another study used adenosine triphosphate testing to evaluate the cleanliness of ultrasound equipment at five facilities in Australia and found that 46.4% of samples of ultrasound gel bottles were dirty-that is, "definitely unclean." 14(p889) If there is concern about cross-contamination, such as when using gel on a patient who requires contact precautions or has a suspected or confirmed COVID-19 infection, 15 personnel should either discard the multidose container after use or use single-use packets. 3,4 Personnel should consider multidose ultrasound transmission gel containers to be high-touch objects 4 when cleaning the environment between patients and clean the container in accordance with facility policy and the manufacturer's IFU.…”
Section: Answermentioning
confidence: 99%
“…If there is concern about cross‐contamination, such as when using gel on a patient who requires contact precautions or has a suspected or confirmed COVID‐19 infection, 15 personnel should either discard the multidose container after use or use single‐use packets 3,4 . Personnel should consider multidose ultrasound transmission gel containers to be high‐touch objects 4 when cleaning the environment between patients and clean the container in accordance with facility policy and the manufacturer's IFU.…”
Section: Sterility Of Ultrasound Transmission Gelmentioning
confidence: 99%
“…Precautions must be rigorous and systematic in the practice of this clinical activity, mainly because there is exposure of the patient and health professionals, given the impossibility of maintaining the recommended distance during the procedure. (1) The information found in this document is based on the best practices recommended by National and International Diagnostic Imaging Societies and guided by two main axes:…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic period changed the routine of obstetric and gynecological ultrasound services, (1) as well as the routine in all other women's health care services. (2,3) Such changes involve a series of protective measures that will be highlighted in this regulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation